The Relationship Between Organizational Climate and Work Discipline for Employees of Company: Hubungan Antara Iklim Organisasi dengan Disiplin Kerja pada Karyawan Perusahaan - Siti Nur Khoiriyah; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by a decrease in employee work discipline. The purpose of this study is to find out and provide an explanation of the relationship between organizational climate and employee work discipline. This research method is quantitative correlation with the subject of PT Galaxy Indah Jaya employees, totaling 163 employees. Determination of the subject using the non-probability sampling technique, namely saturated sampling, where the entire population is used as a sample. The variables in this study are organizational climate and work discipline. The data collection in this study used a psychological preparation scale, namely the Likert scale for organizational climate variables and work discipline variables. Analysis of the data in this study using SPSS 26.0 for Windows. The results of data analysis show that there is a positive relationship between organizational climate and work discipline on employees of PT Galaxy Indah Jaya in Sidoarjo with an rxy value of 0.911, a significance of 0.000. Highlights: The research focuses on the relationship between organizational climate and employee work discipline. The study uses a quantitative correlation research method with PT Galaxy Indah Jaya employees as the subject. Data analysis was conducted using SPSS 26.0 for Windows, revealing a significant positive relationship (rxy = 0.911) between organizational climate and work discipline. Keywords: employee work discipline, organizational climate, quantitative correlation, data analysis, SPSS